Confectionery Recipes from a Fifteenth-Century Manuscript - Banham, Debby; Mason, Laura (Petits Propos Culinaires, 2002)
The contributions which follow are divided into three. The introduction and transcription and translation of the latin  text are by Debby Banham, while Laura Mason has written a commentary. Each section is followed by its own notes and references. The article concerns  confectionary recipes from a 15th-century manuscript, 314/376, held by the library of Gonville & Caius College, Cambridge and puts the material into historical and palaeaographical context -- possibly the only culinary manuscripts surviving from an English Monastic house.